Komunikasi Perseasif Masyarakat Nahdlatul Ulama (NU) dan Muhammadiyah Dalam Membangun Kerukunan Beragama Di Komplek Sidimpuan Baru Kota Padangsidimpuan - RioAnggara (Universitas Muhammadiyah Surabaya, 2025)
This study aims to describe the forms and strategies of persuasive communication employed by the Nahdlatul Ulama (NU) and Muhammadiyah communities in building religious harmony in the Sidimpuan Baru Complex, Padangsidimpuan City. The background of this research is based on the social reality that these two largest Islamic organizations in Indonesia have differences in religious understanding, yet they coexist harmoniously in the community. This study uses a qualitative approach with a case study design. Data were collected through observation, in-depth interviews, and documentation of NU and Muhammadiyah members, community leaders, and local government officials. The results show that the forms of persuasive communication employed include open dialogue, mutual respect for differences, and active involvement in joint social and religious activities. Among the various persuasive communication techniques, the primary strategy used is the integration technique, which emphasizes emotional similarity, social closeness, and the use of inclusive language. Despite differences in worship practices, such as qunut and the number of rak'ahs in tarawih, the community is able to manage these differences peacefully and productively. The harmony created is inseparable from the role of religious and community leaders, as well as local government support, which collectively fosters a climate of tolerance and cooperation. Thus, persuasive communication based on integration has become an essential tool in strengthening inter-religious relationships and creating strong and sustainable religious harmony in the Sidimpuan Baru community.